Tissue-Level Regeneration and Remodeling Dynamics are Driven by Mechanical Stimuli in the Microenvironment in a Post-Bridging Loaded Femur Defect Healing Model in Mice - Paul, Graeme R.; Vallaster, Paul; Rüegg, Michelle; Scheuren, Ariane C.; Tourolle, Duncan C.; Kuhn, Gisela A.; Wehrle, Esther; Müller, Ralph (Frontiers in Cell and Developmental Biology, 2022)
Bone healing and remodelling are mechanically driven processes. While the generalised response to mechanical stimulation in bone is well understood, much less is known about the mechanobiology regulating tissue-scale bone formation and resorption during the reparative and remodelling phases of fracture healing. In this study, we combined computational approaches, in the form of finite element analysis, and experimental approaches, by using a loaded femoral defect model in mice, to investigate the role of mechanical stimulation in the microenvironment of bone. Specifically, we used longitudinal micro-computed tomography to observe temporal changes in bone at different densities, and micro-finite element analysis to map the mechanics of the microenvironment to tissue-scale formation, quiescence (no change in bone presence between time points) and resorption dynamics in the late reparative and remodelling phases (post bridging). Increasing levels of strain led to increasing conditional probability of bone formation, while decreasing levels of strain led to increasing probability of bone resorption. Additionally, analysis of mineralisation dynamics showed both a temporal and strain level dependent behaviour. A logarithmic-like response was displayed, where the conditional probability of bone formation or resorption rose rapidly and plateaued or fell rapidly and plateaued respectively as mechanical strain increased.